On Influence of Fluid Viscosity on Interface Pressure in Hydro-Piezoelectric System Under Its Forced Vibration - Akbarov, S. D.; Ekicioglu Kuzeci, Z. (SPRINGER, 2025)
The primary focus of this paper is to examine the effect of fluid viscosity on vibration that occurs when harmonic mechanical force is applied to a system consisting of a piezoelectric plate, a compressible viscous fluid, and a rigid wall. The exact equations of motion of the linear electro-elasticity theory for the piezoelectric materials are used to describe the plate motion. The plane-strain state of the plate is considered. The linearized Navier-Stokes equations for a compressible (barotropic) viscous fluid are used to describe the fluid flow, and the plane flow is taken into consideration. Equations corresponding to the problem are solved by applying the Fourier transform with respect to the space coordinate, which is on the coordinate axis directed along the plate-lying direction. The Fourier transforms are determined analytically, but the inverse transforms are computed numerically. Numerical results on the interface pressure are obtained for the PMN-PT and PZT-2 materials, and the results are discussed. According to these results, it is established that the fluid viscosity causes the increase in the amplitude of the interface normal stress and can also significantly affect the vibration phase at which the studied stress has its absolute minimum value. Furthermore, the electromechanical coupling effects of the plate material on the studied parameters are determined.
Keywords: piezoelectric plate; forced vibration; fluid viscosity; compressible viscous fluid; coupling effect; COMPRESSIBLE VISCOUS-FLUID; HYDROELASTIC VIBRATION; ELASTIC PLATE; Mechanics